(untitled) (Research, Society and Development, 2022)
Objective: to describe the knowledge of the nursing team about the transfusion process in the Intensive Care Unit. Methodology: a descriptive cross-sectional study, with a quantitative approach. Participated nurses, nursing technicians and nursing assistants who worked in the Intensive Care Unit of a general hospital that is a reference for urgent and emergency care. Results: 44 (80.0%) of the professionals reported not having received previous training in hemotherapy, 39 (70.9%) stated that they do not participate periodically in training that addresses aspects such as transfusion and adverse reactions, and 12 (21.9 %) mentioned knowing the ordinances dealing with the Technical Regulations for Hemotherapeutic Procedures. Anemia (56.9%) and hemorrhage (15.4%) were the most cited responses as an indication for transfusion of red blood cell concentrate. Coagulopathies (35.3%) and thrombocytopenia (57.5%) were the most common indications for the infusion of fresh and concentrated platelet plasma. Chills (69.1%), itching (60.0%), sweating (52.7%), tachycardia (50.9%) and respiratory distress (49.1%) were the most suggestive signs and symptoms of transfusion reactions cited. Only 2 (3.6%) participants correctly mentioned the time of onset of possible complications. Conclusion: there was a deficiency in the knowledge of the nursing team professionals about blood transfusion, as well as the negative impact generated by the lack of training and guidance on the subject in the professionals’ knowledge. It emphasizes the importance of the need for interventions such as continuing and permanent education, as well as the periodic training of professionals of the nursing team on performance in this practice.